Design and performance analysis of cooling tower - Azizul Hafiz, Abdullah; Muhammad Najamuddin, Selamat; Nadzirah, Mohd Mokhtar (2021)
Cooling towers are widely used to dissipate process waste heat into the atmosphere. Based on the direct contact of two of the earth’s most common substances : air and water